2022
DOI: 10.1055/s-0042-1749151
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Measurements of the Sulcus Angle of the Femoral Trochlea in Small-Breed Dogs with and without Medial Patellar Luxation

Abstract: Trochleoplasty is often performed in dogs with medial patellar luxation (MPL); however, the current guidelines on when to perform a trochleoplasty in dogs are vague. The sulcus angle (SA) is used to assess the femoral trochlear morphology in humans. The aim of this study is to describe a method to measure the SA and other parameters of trochlea morphology in dogs using computed tomography. First, we searched for a suitable measuring location for the SA. Transverse images of the femurs were obtained as perpendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…4,28 When comparing our results with the radiographic study of Garnoeva, 8 similar data in terms of mean FTGA in SB dogs without MPL were found, as Garnoeva reported a mean FTGA value of 125 . On the contrary, in the CT study of Sasaki and coauthors, 15 a greater FTGA (135 ± 8 ) was found in SB dogs without MPL. We believe that a plausible explanation to such discrepancy relies on the trochlear position where the FTGA measurement was performed.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…4,28 When comparing our results with the radiographic study of Garnoeva, 8 similar data in terms of mean FTGA in SB dogs without MPL were found, as Garnoeva reported a mean FTGA value of 125 . On the contrary, in the CT study of Sasaki and coauthors, 15 a greater FTGA (135 ± 8 ) was found in SB dogs without MPL. We believe that a plausible explanation to such discrepancy relies on the trochlear position where the FTGA measurement was performed.…”
Section: Discussionmentioning
confidence: 77%
“…We accept our first hypothesis, as in this study the overall FTGA in dogs without MPL was smaller compared to MPL dogs, similarly to what other authors have recently reported. 8,14,15 Among SB and MLB populations, we discovered a mean FTGA of 128 ± 4.7 in SB and 119 ± 5.6 in MLB with cutoff values of 134 and 128 respectively. These data slightly differ from human literature, which suggests that a normal trochlea has an average sulcus angle of 138 ± 6 , while dysplastic trochleae have a sulcus angle >145 .…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations